THE BRECCE DELLA RENGA FORMATION: AGE AND SEDIMENTOLOGY OF A SYN-TECTONIC CLASTIC UNIT IN THE UPPER MIOCENE OF CENTRAL APENNINES. INSIGHTS FROM FIELD GEOLOGY (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 2014)
In the NE Simbruini Mountains, the “Brecce della Renga Fm.” is a clastic unit documenting sedimentation controlled by late Miocene extensional tectonics.The unit has been subdivided into three lithofacies and six sublithofacies, based on the arenite/rudite/pelite ratio. Massive and coarser (up to megablock size) intervals are interpreted as rockfall deposits (likely induced by earthquakes) at the toe of steep submarine escarpments. By contrast, finer levels are interpreted as having been sedimented through avalanching and turbidity flows in more distal settings, and are partly lateral to basinal hemipelagites and siliciclastic turbidites. Pelite lenses, found at various stratigraphic levels, are the result of ponded sedimentation along the clastic margin. Calcareous nannofossils analyses have been performed for age determinations on 60 fossiliferous samples, which were collected in each sublithofacies of the “Brecce della Renga Fm.”. The unit ranges from early Tortonian (MNN8b) to early Messinian (MNN11c). The age and field geometries of the older breccias document the existence of a Tortonian extensional phase, which predated the late Messinian thrusting. A progradation of the clastic wedge can be observed in the Tortonian, while Messinian deposits show a fining upwards trend. The distribution curve of clastics over time can, given the number of synsedimentary faults mapped in the area, be put in relation with the seismicity induced by the activity along such faults, which after reaching an acme in the Tortonian gradually reached a quiescent state in the early Messinian, causing the backstepping of clastic facies.